Opiophobia: A Barrier to Pain Management - Ibtihal M. Alattas (Journal of King Abdulaziz University: Medical Sciences, 2023)
Opiophobia is the physicians’ irrational fear of prescribing opioids for patients with severe pain. It’s one of the major reasons for many patients to not receive adequate analgesia (oligoanalgesia). It’s an old phenomenon that still persists in both developed and developing countries with diff erent rates. This is an unsystematic literature review of studies that have been written about opiophobia since 1960 using Google Scholar, PubMed and EBSCO to search for the following terms: opiophobia, oligoanalgesia and necrophobia. Studies included were review articles and surveys studies. We found that the three main reasons for opiophobia are concern over addiction, concern over serious side eff ects (mainly respiratory depression) and concern over legal consequences. These consequences, such as being sued, result from serious side eff ects masking or delaying the diagnosis. Lack of knowledge about pain management was another factor among young physicians and interns. As a result, many patients are not adequately treated for severe pain. Physicians prescribe lesser dosages than required and nurses administer even lesser dosages than the physicians prescribed. To tackle such problems, it’s important to know the causes. Education, clarifi cation of the myths and increasing the physicians’ and nurses’ awareness about pain management is a critically important step especially for new physicians and interns.